Romania’s Implication in the Global Financial Cycle - Gurgu, Elena; COCIUBAN, Aristide (Annals of Spiru Haret University. Economic Series, 2016)
In this article we intend to approach the global financial cycle and the international production networks, as well as Romania’s international investment position through its main components. The targets relate to: the global financial cycle and the recent experience of emerging economies, describing global production networks, the implications of extending international production networks, the influence of trade integration on economic development. Also, we approach the evolution of investments in our country in 2015, with reference to international reserves, gross external debt and net external debt. Drawn conclusions refer to mitigating the contagion effects generated by the increase of the degree of global financial integration.